URGENSI PENERAPAN PIDANA MATI DI INDONESIA (Telaah Terhadap Pelaku Pencurian Sepeda Motor Menggunakan Kekerasan) - Ade Indriyuni (Muhammadiyah Law Review Journal, 2020)
The development of the current era shows that the perpetrators of theft with violence or other crimes are increasingly rampant. Indonesia often happens theft with objects of goods namely motorcycles, the perpetrators of theft do not hesitate to kill victims to get the stolen goods, the actions of thieves are criminal acts. Article 10 of the Criminal Code regulates the type of punishment, one of which is capital punishment. The problem in this research is how to implement the death penalty on the perpetrators of theft by motorized vehicle violence and how the efforts to reduce the crime crime rate. The method used in this study is a normative juridical approach and at the same time a sociological approach is carried out as a study of law in society. The results of this study indicate that the application of the death penalty against perpetrators of theft by violence that resulted in serious injuries to the victims even to the loss of the victim's life has not been carried out in accordance with the provisions of the existing laws and regulations in Indonesia. Of the many cases of theft with violence that occurred in Indonesia, only a few carried out the application of the death penalty. This shows that Article 365 paragraph 4 of the Criminal Code that provides provisions for the execution of the perpetrators of theft by violence until the loss of the victim's life has not run optimally. Thus the law enforcers must make efforts in preventing the criminal acts of theft by violence so as not to increase.